Violência financeira contra a pessoa idosa: os desencontros da velhice. - Silva, Sonia Maria Ortiz da (2018)
The central theme of this research is old age, with emphasis on violence against the elderly and, in particular, financial violence. The problem that guided this research was: what are the elements and impacts of financial violence suffered by the elderly population in face of the contradictions and antagonisms produced by capitalist society? The objective of this research was to understand and analyze the elements and impacts of financial violence against elderly people assisted by the CREAS/CRAM of the municipality of Umuarama-PR, in the period of 2015 and 2016. Having as method of approach the scientific method, the research process was based on the qualitative, exploratory and bibliographical research, in the case study and in the documentary research by means of analysis in the assistance records for the elderly inserted in the CREAS/CRAM service, in the years 2015 and 2016. Based on the research, it was possible to identify that, in the delimited time frame, 190 cases of elderly people in situation of violation of rights were inserted, being that the universe of the research. From this universe, we identified that 27 cases of complaints received were of financial violence, however, when analyzing the records, we identified that the complaint proceeded in 18 of the cases. Thus, we have the sample of the research, that is, 18 assistance records for the elderly in situations of financial violence. After the analysis, as well as the study of authors investigating the subject matter, it was possible to verify the hypothesis formulated – financial violence against the elderly is the result of a capitalist culture present in contemporary social relations that are accentuated before a consumer culture, individuality and loss of the sense of the common good, leading to the fragility of the elderly's well-being – to answer the research problem. Research has shown that the hypothesis has been confirmed, since the analysis of the content indicates that financial violence against the elderly is intertwined with the capitalist system culture present in contemporary social relations. Therefore, the relationship of power and the scarcity of respect have their roots in capitalist culture, which generates social inequality and creates and recreates ideologies of individualism, selfishness, disrespect, consumerism, competitiveness and domination.